Electric Field Mediated Instabilities for On-Demand Microfluidic Mixing and Separation - Dutta, Satarupa (My University, 2021)
The thesis deals with the study of the effects of externally applied electric field in some selected microfluidic phenomena with the aid of micro and mesoscale model set-ups. Experiments as well as theoretical studies shed light on the physics governing the phenomena along-with demonstrating the feasibility of the same for various practical applications. Microfluidic Mixing: The characteristics of electric field induced instabilities triggered due to ion injections in stratified miscible microflows for prospective applications of mixing, micro-reactions and enhancement of heat and mass transfer operations are studied. A complete linear stability analysis and numerical simulations of the phenomena reveal the finer details of such instabilities. Particle Laden Flows: Th salient features of the electric field induced assemblies of microparticles suspended in an insulating liquid have been studied. With the use of a mesoscale set-up, the charge transfer dynamics associated with the field induced multi-particle oscillations have been studied experimentally. Numerical simulations have been carried out to explore the physics associated with the phenomena. Droplet Laden Flows: The dynamics associated with the electric field driven migrations of an aqueous droplet across the interface between liquid pairs with very low interfacial tensions between them have been studied. A combined experimental and numerical study explores the various modes of such active migrations along-with characterising the idiosyncrasies associated with them. In another study, the asymmetric contact dynamics during electric field induced drop non-coalescence in an insulating oil have been explored with the help of experiments and numerical simulations.
Bandyopadhyay, Dipankar
Pattader, Partho Sarathi Gooh
Keywords: CHEMICAL ENGINEERING